2007
DOI: 10.1177/1049909106295385
|View full text |Cite
|
Sign up to set email alerts
|

Should Age Limit Admission to the Intensive Care Unit?

Abstract: People who are older than 65 years of age are the fastest growing segment of the United States population. With the projected exponential increase in the number of elderly patients and the increasing burden of chronic disease, the number of elderly patients who will require treatment in an intensive care unit is expected to increase. Owing to the elderly patient's reduced life expectancy and higher intensive care unit and hospital mortality, it could be argued that elderly patients should not be admitted to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
(15 reference statements)
1
12
0
1
Order By: Relevance
“…Annual reporting and statistical analyses were supported by Sanofi-Aventis (years 2006 and2007), the Ministry of Health, Social Services and Equality (year 2008), Novartis (years 2009 and 2010) and Pfizer (year 2011) but none of these pharmaceutical companies and the governmental body participated in the any phases of the study or interpretation of the results. …”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Annual reporting and statistical analyses were supported by Sanofi-Aventis (years 2006 and2007), the Ministry of Health, Social Services and Equality (year 2008), Novartis (years 2009 and 2010) and Pfizer (year 2011) but none of these pharmaceutical companies and the governmental body participated in the any phases of the study or interpretation of the results. …”
Section: Conflict Of Interestmentioning
confidence: 99%
“…[16][17][18][19] Some authors have suggested that age alone should not be used as a factor when considering admission. [20] The physiological age of a patient, or an assessment of frailty, may be more important than chronological age. [21] Even though age was considered as a factor in admission decisions in another study, 95.1% of physicians indicated that a definitive age criterion precluding ICU admission should not be instituted.…”
Section: Researchmentioning
confidence: 99%
“…SF-36 scores were collected to compare with the pre-admission CPAx scores. Furthermore, as recovery from critical illness is associated with pre-admission health status [23,24], the SF-36 score was also compared with the CCU discharge CPAx score.…”
Section: Number Of Days Of Mechanical Ventilationmentioning
confidence: 99%